Pengaruh Sudut Part Build Orientation Z-Direction Terhadap Kuat Tarik Spesimen Uji Standar Astm D638 Type IV Menggunakan Filamen Pla+ - Pristiansyah, Pristiansyah; Yuliyanto, Yuliyanto; Masdani, Masdani; Sirwansyah Suzen, Zaldy; Kurniawan, Zaldy; Sugianto, Sugianto; Hasdiansah, Hasdiansah; Feriadi, Indra; Pranata, Yogi; Napitupulu, Robert; Harwadi, Harwadi (Manutech : Jurnal Teknologi Manufaktur, 2023)
This study will try to investigate variations in the angle of the Z-direction build part by using a 3D Printer with Fused Deposition Modeling (FDM) technology made from PLA + Sugoi. This study uses a 0.4mm nozzle with a Bowden type extruder. This study uses a PLA+ filament from the Sugoi brand with a nozzle of 0.4 mm, diameter filament 1,75 mm, 3D Printer with Fused Deposition Modeling (FDM) technology used is Creality Ender 3 V2 with process parameter settings in slicing software using a layer thickness of 0.30 mm, Top solid Layer 5, Bottom Solid Layer 5, Fill density 100%, cooling speed 100%, and flowrate 100%, nozzle temperature 205°C, and bed temperature 60°C. Variation in angle Part build Z-direction is proven to have a significant difference in Tensile strength with a difference of 10° resulting in a difference in Tensile strength of 15 MPa, where the highest tensile strength is 67.50 MPa with part build Z-direction at an angle of 80°, and the lowest tensile strength of 52.50 MPa with a Z-direction part build angle at an angle of 70°.